2019
DOI: 10.1155/2019/3024965
|View full text |Cite
|
Sign up to set email alerts
|

Application of Optimal Control Theory to Newcastle Disease Dynamics in Village Chicken by Considering Wild Birds as Reservoir of Disease Virus

Abstract: In this study, an optimal control theory was applied to a nonautonomous model for Newcastle disease transmission in the village chicken population. A notable feature of this model is the inclusion of environment contamination and wild birds, which act as reservoirs of the disease virus. Vaccination, culling, and environmental hygiene and sanitation time dependent control strategies were adopted in the proposed model. This study proved the existence of an optimal control solution, and the necessary conditions f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…Studies show that seasonality of outbreaks is influenced by changes in climatic conditions leading to stress, which predisposes birds to the disease, and hot, dry and windy periods, which encourage airborne spread of the virus ( 27 ). Several studies in sub-Saharan Africa settings have shown the substantial losses due to NCD in village poultry systems ( 28–30 ) resulting from high mortalities ( 11 ). Dankwa et al ( 31 ) in their study of Northern Ghana show recurrent outbreaks of NCD in November and January and resulting losses of flocks.…”
Section: Discussionmentioning
confidence: 99%
“…Studies show that seasonality of outbreaks is influenced by changes in climatic conditions leading to stress, which predisposes birds to the disease, and hot, dry and windy periods, which encourage airborne spread of the virus ( 27 ). Several studies in sub-Saharan Africa settings have shown the substantial losses due to NCD in village poultry systems ( 28–30 ) resulting from high mortalities ( 11 ). Dankwa et al ( 31 ) in their study of Northern Ghana show recurrent outbreaks of NCD in November and January and resulting losses of flocks.…”
Section: Discussionmentioning
confidence: 99%
“…Consider an optimal problem of system (1) , subject to initial conditions of state variable and boundary condition of control variables u i ( t ) ∈ U for i = 1, …, 4 . There exists an optimal solution such that if the following necessary conditions in ( Chuma, Mwanga, & Masanja, 2019 ) are satisfied: Control set U and the corresponding state variables are nonempty, Control set U is convex and closed, The right hand side of the state system is bounded by the linear function in the state and control variables, The integrand of the objective function is convex, and There exist constant numbers q 1 , q 2 > 0 and ξ > 1 such that the integrand of the objective function is bounded below by . …”
Section: Formulation Of Optimal Control Problemmentioning
confidence: 99%
“…where A 1 , A 2 , and A 3 are the weight constants associated with the number of susceptible individuals, the number of individuals infected with drug-sensitive strain, and the number of individuals infected with drug-resistant strain while B 1 , B 2 , B 3 , and B 4 present relative cost weight which is associated with control measures u 1 , u 2 , u 3 , and u 4 , respectively. The control variables in the objective functional are in quadratic form because we assume that costs are nonlinear in nature which is a convex function as applied by [17,[33][34][35]. The aim is to minimize the objective functional such that the optimal control satisfy…”
Section: A Model For the Optimal Control Problemmentioning
confidence: 99%